1997
DOI: 10.1088/0953-8984/9/36/009
|View full text |Cite
|
Sign up to set email alerts
|

The magnetism of at low fields

Abstract: Magnetic susceptibility and magnetization measurements were made on a polycrystalline sample of . The compound is ferromagnetic for at any applied magnetic field. For temperatures between and and magnetic fields smaller than a critical field , the compound is helimagnetic. When or , the anisotropy in the basal plane increases, and the compound becomes ferromagnetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Thus, we can conclude that the two phase model of the TbNi 5 magnetic structure as suggested in Refs. [14,15] is not correct.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, we can conclude that the two phase model of the TbNi 5 magnetic structure as suggested in Refs. [14,15] is not correct.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the resistivity data authors of Ref. [14] concluded that a critical field was m 0 H fer ¼ 3 kOe. A discrepancy in the critical field values they explained by a high demagnetization factor of parallelepipedic form of a specimen used in their resistivity measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations